KOLABORASI IMPLEMENTASI PROGRAM BPNT DALAM PENANGANAN KEMISKINAN DI DESA KARETAN KECAMATAN PURWOHARJO KABUPATEN BANYUWANGI - Salsabila, Anis; Priyanto, Hary; Vitasari, Leni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2024)
Collaboration on the Implementation of the BPNT Program in Handling Poverty in Karetan Village, Purwoharjo District, Banyuwangi Regency. This study aims to identify and describe the handling of poverty through the implementation of the BPNT program in Karetan Village. The importance of this research is because there is a phenomenon of the distribution of BPNT that is not well targeted in Karetan Village. This research uses a qualitative descriptive approach, which is carried out intensively, in-depth, in detail and comprehensively. The research sources used primary data and secondary data which were managed based on saturated data and analyzed based on the thoughts of Albrecht and Zemke. The results of this study are that the strategies carried out by the Karetan Village Government are less than optimal in dealing with poverty and the distribution of aid that is not well targeted; the need to be guided by the correctness of the data and the compliance of the Karetan Village Government with laws and regulations, service procedures related to facilities needed by the community; improving the quality of human resources for officers, because not all existing human resources have the qualifications and understanding related to the main tasks and procedures; less than the maximum service provided by the Karetan Village Government to the community. The implementation of the Karetan Village Government in reducing poverty needs to be evaluated from the aspect of strategy, system, and better human resources, so that it has an impact on the welfare of the Karetan Village community.